Impact of population growth on Carbon Dioxide (CO2) emission: empirical evidence from Nigeria - Ibrahim Mohammed Lawal (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This paper seeks to examine the impact of population growth on carbon dioxide emission in Nigeria. Time series data from 1975 to 2016 was adopted. Variables such as population, affluence and technology were used as independent variables which were extracted from the IPAT equation. Econometric tools such as Ordinary Least Squares were adopted. The findings show that there is a positive association between CO2 emission, population and technology whereas affluence has a negative relationship with CO2. The study concluded that the population growth has a marginal impact on the level of CO2 emission. The paper recommended that there is need for the government to adopt a climate friendly technology that will minimize the increasing CO2 emission, improve on its GDP alongside controlling her population growth.